P-325 Social Stressor Exposure in C57BL/6 Mice Impacts Inflammation, Microbiota, Short Chain Fatty Acids in a Murine Model of Colitis. (February 2017) - Maltz, Ross; Keirsey, Jeremy; Mackos, Amy; Kim, Sandra; Somogyi, Arpad; Gharaibeh, Raad; Moore, Cathy; Bailey, Michael
Abstract : Background: Exposure to stress has been associated with the development of inflammatory bowel diseases (IBD) and triggering disease exacerbation. The mechanisms are not clearly defined, but exposure to stressors has been shown to induce inflammatory cytokines and chemokines, and to change the composition of the gut microbiota in murine models of colitis. Short chain fatty acids (SCFAs) are produced by gut microbiota, and activation of SCFA receptors can influence the acute inflammatory response. Determine if SCFAs mediate the link between social stressor exposure, the gut microbiota, and increased colonic inflammatory responses in Citrobacter rodentium-infected mice. Methods: Male specific pathogen-free C57BL/6 mice 6- to 8-week-old were either infected with C. rodentium or left uninfected (control group). In addition, mice were either exposed to a social stressor known as social disruption (SDR) or left unstressed. SDR involves repeated social defeat over a 2 hour period; this process is repeated on 6 consecutive days. Mice were infected after the first exposure to SDR. Tissue was harvested on day 6 or day 12 post-infection. Semi-quantitative real time PCR was performed on proximal colonic tissue to assess the expression of inflammatory cytokines (TNF-α, IL-1β, and iNOS), anti-inflammatory cytokines (TGF-β and IL-10), and mRNA levels of SCFA receptors (GPR41, GPR43, and GPR109). Fecal samples taken from the colon on the day of the tissue harvest were extracted to quantify SCFA levels (acetic acid, butyric acid, and propionic acid) by gas chromatography-mass spectrometry (GC-MS). DNA was extracted from colonic tissue, amplified targeting the V3-4 regions of the 16S rRNA gene and sequenced via the Illumina MiSeq. Results: Exposure to the stressor affected the beta diversity, and exposure to the pathogen affected the alpha and beta diversity ( P < 0.05). Stressor and pathogen exposure significantly increased inflammatory markers (iNOS and TNFα mRNA [ P < 0.05]), and histology scores ( P < 0.05). Stressor exposure decreased the relative abundance of 7 genera and increased 5 genera ( P < 0.05). Mice challenged with C. rodentium decreased the relative abundance of 11 genera and increased the abundance of 4 genera ( P < 0.05). Stressor and/or pathogen exposure decreased the relative abundance of Akkermansia, Coprococcus, Butyricicoccus, Parabacteroides, Bacteroides, Oscillospira, and Roseburia which are associated with decreased abundance in patients with IBD. Stressor exposure caused a decrease in acetic acid and butyric acid on day 6 ( P < 0.05) without pathogen exposure; when exposed to both stressor and pathogen, acetic acid, butyric acid, and propionic acid increased on day 6 ( P < 0.05). Pathogen exposure resulted in reduced GPR43 receptor mRNA expression ( P < 0.05) regardless of stressor exposure. Expression of GPR41 and GPR109A receptor mRNA increased with pathogen exposure, but only if the mice were exposed to the SDR stressor ( P < 0.05). Conclusions: Stressor exposure and challenge with C. rodentium significantly changed the composition of the gut microbiota. The relative abundance of multiple genera found to be decreased in patients with IBD were also decreased after stressor and/or pathogen exposure. Our data indicates that a social stressor can have a profound effect on the microbiota, SCFAs and receptor signaling on colonic inflammation when exposed to a pathogen.